1947
DOI: 10.1152/ajplegacy.1947.149.3.552
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Acute Hypothermia on the Rate of Oxygen Consumption and Glycogen Content of the Liver and on the Blood Glucose

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1954
1954
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…2 the blood glucose of rats significantly increased during the early phase of hypothermia. This observation is in accord with those of FUHRMAN andCRISMON (1947) andPOPOVIC (1960). The former authors found that the increase in blood glucose was observed only for fed rats.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…2 the blood glucose of rats significantly increased during the early phase of hypothermia. This observation is in accord with those of FUHRMAN andCRISMON (1947) andPOPOVIC (1960). The former authors found that the increase in blood glucose was observed only for fed rats.…”
Section: Discussionsupporting
confidence: 91%
“…Blood glucose and free fatty acids are known as the major fuels for shivering thermogenesis, the primary means of heat production in acute cold exposure in rats . Changes in energy substrates for heat production have been investigated for hypothermic homeotherms (FUHRMAN and CRISMON, 1947;PoPoviC, 1960;DEPOCAS, 1962). However, no measurements have been reported on the simultaneous variations in the gas exchange and energy substrates metabolism during hypothermia.…”
mentioning
confidence: 99%
“…Hypothermic-related serum amylases elevations, leading to oedematous or necrohemorrhagic pancreatitis, is often found in necropsy studies of hypothermic patients [15]. The relationship between pancreatitis and hypothermia has not yet been solved, although it has been implicated in ischemia secondary to shock, previous and abusive alcohol intake or the presence of gallstones [15,26].…”
Section: Body Temperature Regulationmentioning
confidence: 99%
“…Hypothermic-related serum amylases elevations, leading to oedematous or necrohemorrhagic pancreatitis, is often found in necropsy studies of hypothermic patients [15]. The relationship between pancreatitis and hypothermia has not yet been solved, although it has been implicated in ischemia secondary to shock, previous and abusive alcohol intake or the presence of gallstones [15,26]. Other gastrointestinal alterations that can be found in hypothermia are: Multiple punctate erosions of low haemorrhagic (Wischnevsky ulcers) in the stomach, ileum and colon; probably related to the release thologies, mortality can reach up to 75% [15].…”
Section: Body Temperature Regulationmentioning
confidence: 99%
See 1 more Smart Citation